PENGARUH SUMBER BELAJAR DIGITAL DAN GAYA BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) - Syahril Syahril; Mukhamad Ilyasin; Fathul Janah (STKIP PGRI Situbondo, 2024)
The research background is the development of student learning outcomes in Islamic Religious Education (PAI) subjects, which, if seen from the influence of digital learning resources and student learning styles, shows how much influence they have on student learning outcomes, the aim of this research is: Analyzing digital learning resources, Analyzing student learning styles and Analyzing learning outcomes and Analyzing the magnitude of the influence of digital learning resources on PAI learning outcomes of students, Analyzing the magnitude of the influence of learning styles on PAI learning outcomes of students and Analyzing the magnitude of the influence of digital learning resources and learning styles on PAI. This type of research uses quantitative research, the location of this research is at two SMKN 1 Samarinda and SMKN 4 Samarinda, with the number of respondents being 145 students at two SMKN 1 and SMKN 4 Samarinda, all of them are class XI students, data analysis uses descriptive statistical data analysis (analysis mean/average), Regression analysis with t test and F test, data analysis process using the SPSS version 24 application. The results of research on finding (1). The influence of digital learning resources on PAI learning outcomes is 29.40%. and the Sig value is 0.024 <0.05 and the first hypothesis is concluded to be accepted. (2). The magnitude of the influence of learning style on PAI learning outcomes is 49.50%, the Sig value is 0.000 < 0.05. The second hypothesis is accepted and (3) The magnitude of the influence of digital learning sources and learning styles on PAI learning outcomes is 51.30%. The Sig value for the influence of X1 and X2 on Y is 0.000 < 0.05 The third hypothesis is accepted. Tujuan penelitian ini adalah mengetahui besarnya pengaruh sumber belajar digital terhadap hasil belajar PAI, mengetahui besarnya pengaruh gaya belajar terhadap hasil belajar PAI dan mengetahui besarnya pengaruh sumber belajar digital dan gaya belajar terhadap hasil belajar PAI. Jenis penelitian ini menggunakan penelitian kuantitatif, tempat penelitian ini adalah pada dua SMKN 1 Samarinda dan SMKN 4 Samarinda, dengan jumlah responden adalah 145 siswa pada dua SMKN 1 dan SMKN 4 Samarinda, semuanya siswa kelas XI, analisa data menggunakan analisis data statistic deskritif (analisis mean/rata-rata) dan analisis Regresi dengan uji t dan uji F, proses analisis data menggunakan aplikasi SPSS versi 24. Hasil penelitian tentang menemukan (1). Besar pengaruh sumber belajar digital terhadap hasil belajar PAI sebesar 29,40%.  dan nilai Sig sebesar 0,024 < 0,05 dan hipotesis kesatu disimpulkan diterima. (2). Besarnya pengaruh gaya belajar terhadap hasil belajar PAI sebesar 49,50% nilai Sig sebesar 0,000 < 0,05. Hipotesis kedua diterima dan (3) Besarnya pengaruh sumber belajar digital dan gaya belajar terhadap hasil belajar PAI adalah sebesar 51,30%. Nilai Sig untuk pengaruh X1 dan X2 terhadap Y adalah sebesar 0,000 < 0,05 Hipotesis ketiga diterima.